The effect of relativism ethical orientation, personal cost, and moral intensity on internal whistleblowing intention: the moderating role of organizational commitment - ., Hardi; Wiguna, Meilda; Anita, Rizqa; Balkish Zakaria, Nor (International Journal of Engineering and Technology, 2018)
This study attempts to examine the moderating effect of organizational commitment on the relationship between relativism ethical orientation, personal cost, moral intensity and internal whistle blowing intention. Using multiple regression as analytical method, responses from 104 employees of Rokan Hulu Regency, Indonesia were analyzed. The results of this research show that relativism ethical orientation of negatively effecting internal whistle blowing intention, personal cost does not affect internal whistle blowing intention, moral intensity affect internal whistle blowing intention, and organizational commitment affect the relationship between the relativism ethical orientation and internal whistle blowing intention. The findings of this study also suggest that commitment organization does not affect the relationship between personal cost and internal whistle blowing intention, and commitment organization affect the relationship between moral intensity on internal whistle blowing intention.Â